Symmetry-breaking in the endofullerene H2O@C60 revealed in the quantum dynamics of ortho and para-water: a neutron scattering investigation - Goh, Kelvin S.K.; Jimenez-Ruiz, Monica; Johnson, Mark R.; Rols, Stephane; Ollivier, Jacques; Denning, Mark S.; Mamone, Salvatore; Levitt, Malcolm H.; Lei, Xuegong; Li, Yongjun; Turro, Nicholas J.; Murata, Yasujiro; et al. (Royal Society of Chemistry, 2014)
Inelastic neutron scattering (INS) has been employed to investigate the quantum dynamics of water molecules permanently entrapped inside the cages of C60 fullerene molecules. This study of the supramolecular complex, H2O@C60, provides the unique opportunity to study isolated water molecules in a highly symmetric environment. Free from strong interactions, the water molecule has a high degree of rotational freedom enabling its nuclear spin isomers, ortho-H2O and para-H2O to be separately identified and studied. The INS technique mediates transitions between the ortho and para spin isomers and using three INS spectrometers, the rotational levels of H2O have been investigated, correlating well with the known levels in gaseous water. The slow process of nuclear spin conversion between ortho-H2O and para-H2O is revealed in the time dependence of the INS peak intensities over periods of many hours. Of particular interest to this study is the observed splitting of the ground state of ortho-H2O, raising the three-fold degeneracy into two states with degeneracy 2 and 1 respectively. This is attributed to a symmetry-breaking interaction of the water environment.